Genetic and Phenotypic Features of a Novel Acinetobacter Species, Strain A47, Isolated From the Clinical Setting - Schramm, Sareda T. J.; Place, Kori; Montaña, Sabrina; Almuzara, Marisa; Fung, Sammie; Fernandez, Jennifer S.; Tuttobene, Marisel R.; Golic, Adrián; Altilio, Matías; Traglia, German M.; Vay, Carlos; Mussi, Maria Alejandra; et al. (Frontiers in Microbiology, 2019)
In 2014, a novel species of Acinetobacter, strain A47, determined to be hospital-acquired was recovered from a single patient soft tissue sample following a traumatic accident. The complexity of the Acinetobacter genus has been established, and every year novel species are identified. However, specific features and virulence factors that allow members of this genus to be successful pathogens are not well understood. Utilizing both genomic and phenotypic approaches, we identified distinct features and potential virulence factors of the A47 strain to understand its pathobiology. In-silico analyses confirmed the uniqueness of this strain and other comparative and sequence analyses were used to study the evolution of relevant features identified in this isolate. The A47 genome was further analyzed for genes associated with virulence and genes involved in type IV pili (T4P) biogenesis, hemolysis, type VI secretion system (T6SS), and novel antibiotic resistance determinants were identified. A47 exhibited natural transformation with both genomic and plasmid DNA. It was able to form biofilms on different surfaces, to cause hemolysis of sheep and rabbit erythrocytes, and to kill competitor bacteria. Additionally, surface structures with non-uniform length were visualized with SEM and proposed as pili-like structures. Furthermore, the A47 genome revealed the presence of two putative BLUF type photoreceptors, and phenotypic assays confirmed the modulation by light of different virulence traits. Taken together, these results provide insight into the pathobiology of A47, which exhibits multiple virulence factors, natural transformation, and the ability to sense and respond to light, which may contribute to the success of an A47 as a hospital dwelling pathogen.